“EFFORTS TO INCREASE CUSTOMER LOYALTY OF BANK INDONESIAN SYARIAH OFFICE OF THE MAIN BRANCH OF BANDUNG BY INCREASING PERFORMANCE OF PHYSICAL EVIDENCE, PROCESS AND PEOPLE” - Rachmawati, Mariana; , Veronica; , Herdiawan; Sinaga, Obsatar (CENTRAL ASIA AND THE CAUCASUS, 2022)
The service industry is one of the business sectors that has a competitive level of business competition. One service industry that faces high competition is the banking sector. The condition of banks in Indonesia is currently growing and shows an increasingly competitive level of competitiveness. Bank Syariah Indonesian is one of the companies engaged in the Indonesian banking sector. One of the main businesses of . Bank Syariah Indonesian is consumer lending. This study aims to determine the effect of physical evidence, process and people on the debtor loyalty of Bank Syariah Indonesian di Bandung both partially and simultaneously. The research method used is the explanatory method.. The data analysis technique used is multiple linear regression analysis. The results of the study show that physical evidence, process, people and debtor loyalty are included in the "Low" condition. Partially the evidence physical process, process, people have a positive and significant influence on customer loyalty. Simultaneously, physical evidence, process, and people influence customer loyalty. Suggestions for proposed improvements to the management of Bank Syariah Indonesian include improvements in terms of people by increasing the number of loan officers by first taking into account the cost and benefit aspects, providing special service space for retired customers, conducting product assessments regularly and disseminating information / updating credit provisions the latest.